Negotiating public and community media in post-Suharto Indonesia - Gazali, Effendi (Javnost (Ljubljana), 2003)
Indonesia and its media are going through a rapid stage of transition. While the goal of this reform movement is the transition to a civil society and creation of a more democratic media system, the main result so far has been the liberalisation of the media market, in line with global media trends, which as such does not necessarily guarantee a more democratic communication system. One way to counter this development is though the decentralisation of radio and television, and the establishment of public and community media, which was under discussion in the Indonesian Parliament. This article presents the results of a qualitative research project carried out in several regions throughout Indonesia, which gave local people a platform to voice their ideas on the media portrayal of their "multiple identities" (e.g., cultural, political, economic, or ethnic), and their perception of the "viability" (problems, prospects, and promises) of alternative broadcasting in relation to the state and commercial broadcasters.
Keywords: Indonezija; radio; tranzicija; demokratizacija; civil society; civilna družba; mass media; množični mediji; television; televizija; trg; medijska politika